The Dare Game - Wilson, Jacqueline and Sharratt, Nick (London Corgi Yearling, 2006)
Tells the story of Tracy Beaker, the great inventor of extremely outrageous dares. Tracy has no designer clothes, when she really needs them. No wonder she bunks off. Still, it will have to do until her real mum comes and gets her. And until then, no-one is going to be better at the Dare Game than Tracy Beaker.
Include Illustrations
Keywords: Children--Institutional care